Adaptive time division duplexing network with network coding embedded two-way relay - Hu, Sanqing; Yao, Yu-Dong (IET communications, 2014)
Using relays to receive and forward packets between a network base station and network users is a promising solution to address the cellular coverage issue. In this study, we consider time division duplexing (TDD) networks and explore the use of network coding for implementing the relays. Several transmission scenarios are investigated, including direction transmissions, one-way relay and two-way relay. In addition, we propose an adaptive TDD network, which enables the network to adaptively configure frame structures based on channel conditions to support direct transmissions, cooperative relay and two-hop relay (one-way and two-way). An opportunistic decoding scheme and a relay operation scheme are introduced to realise the proposed adaptive TDD network in a distributed manner. Both throughput and outage probability are derived. Performance evaluations show that the proposed adaptive TDD network based on network coding achieves the maximum throughput, as compared with one-way relay (without network coding), and extends the cell coverage range (compared with direct transmissions).